Revision of the Afrotropical species of Dohrniphora DAHL (Diptera: Phoridae) - Disney, R. Henry L. (Zootaxa, 2003)
The hitherto unknown male of Dohrniphora angolensis Beyer is described and D. schmitzi Kohl is synonymized with the Oriental D. papuana (Brues) and the following new species are described:- D. aseta from Malawi, D. confusa from the Seychelles, D. gouteuxi from Ivory Coast, D. hararensis from Zimbabwe, D. harteni from Yemen, D. ivoriensis from the Ivory Coast, D. malawiensis, D. montana and D. stuckenbergi from the Malawi, D. zambiae from Zambia and D. zophera from Yemen and Zambia, are described. A new key to all the males of the Afrotropical Region is provided.